Dear Mothman - Gow, Robin (Amulet Books, 2023)
After his best friend Lewis, the only other trans boy at school, dies in a car accident, sixth-grader Noah starts writing letters expressing his feelings to Lewis's favorite humanoid creature Mothman, and risks everything when he treks into the woods to prove Mothman's existence for his science fair project.